2007
DOI: 10.1016/j.bbrc.2006.12.151
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and Sp1 binding determine the tissue-specific transcriptional activity of the mouse Abcc6 promoter

Abstract: SummaryThe gene encoding the ABCC6 protein, an ABC transporter of the multidrug resistance-associated protein (MRP), is mainly expressed in liver and kidney. Mutations in ABCC6 are responsible for the development of the pseudoxanthoma elasticum (PXE) phenotype. PXE is a recessive disease characterized by the calcification of elastic fibers resulting in dermal, vascular and ocular clinical manifestations. The physiological function of ABCC6 and the rodent orthologs Abcc6 is unknown and their precise relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
60
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 34 publications
6
60
1
Order By: Relevance
“…In WT liver extracts, we found that the relative amount of DNA pulled down with antibodies to NF-E2, Sp1, and HNF4␣ were 1.5-to 2.5-fold greater than those in negative controls, indicating an association of these TFs with the Abcc6 proximal promoter ( Figure 6). As expected, 12,23 pull-down results obtained with HNF1␣ and MTF-1 showed no major association. When chromatin immunoprecipitation assay was carried out with Hbb th3/ϩ liver extracts, we found similar results for HNF1␣, Sp1, and HNF4␣ when compared to WT levels ( Figure 6).…”
Section: S1a See Http://ajpamjpatholorg)supporting
confidence: 79%
See 1 more Smart Citation
“…In WT liver extracts, we found that the relative amount of DNA pulled down with antibodies to NF-E2, Sp1, and HNF4␣ were 1.5-to 2.5-fold greater than those in negative controls, indicating an association of these TFs with the Abcc6 proximal promoter ( Figure 6). As expected, 12,23 pull-down results obtained with HNF1␣ and MTF-1 showed no major association. When chromatin immunoprecipitation assay was carried out with Hbb th3/ϩ liver extracts, we found similar results for HNF1␣, Sp1, and HNF4␣ when compared to WT levels ( Figure 6).…”
Section: S1a See Http://ajpamjpatholorg)supporting
confidence: 79%
“…At 10 months, Abcc6 expression had dropped to 55% of the wild-type levels and at 14 months, the mRNA expression had further decreased to 44%. Despite levels much lower than in the liver, 12 the kidney expression profile in Hbb th3/ϩ mice presented no major difference when compared to WT mice ( Figure 1B) (P Ͼ 0.2). We also evaluated the level of Abcc6 expression in the small intestine at 10 months and found no change between WT and Hbb th3/ϩ mice ( Figure 1C).…”
Section: Abcc6 Mrna Levels In Hbb Th3/ϩ Micementioning
confidence: 89%
“…We have also identified by luciferase assay a silencer and a DNA methylation-dependent activator sequence in this conserved region. Several transcription factors have been implicated later in the regulation of the human and mouse ABCC6 genes based on luciferase reporter gene experiments (15)(16)(17)(18)(19). More recently, it has been proposed, that the ABCC6 promoter polymorphisms may be functionally linked to PXE (20) and our results suggested that these polymorphisms are modulating the binding capacity of previously identified transcription factors (21).…”
supporting
confidence: 58%
“…In this initial study on the regulation of the gene we reported an inverse correlation between the CpG island hypermethylation located in the conserved proximal promoter and the expression of the gene in various cell lines (14). This finding was confirmed in mouse tissues (15). We have also identified by luciferase assay a silencer and a DNA methylation-dependent activator sequence in this conserved region.…”
mentioning
confidence: 62%
“…However, numerous studies have demonstrated the critical importance of knowing the methylation status of individual CpG sites, which can vary even when in very close proximity to apparently invariable methylcytosines (Prendergast and Ziff 1991;Weaver et al 2004Weaver et al , 2007. Inhibition of binding of the SP1 transcription factor and the insulator protein CTCF by cytosine DNA methylation within their binding elements has been extensively documented (Clark et al 1997;Kitazawa et al 1999;Mancini et al 1999;Bell and Felsenfeld 2000;Hark et al 2000;Inoue and Oishi 2005;Douet et al 2007). It was recently demonstrated that RNA-directed DNA methylation of a single CpG located within a putative conserved intronic cis element of the Petunia floral homeotic gene pMADS3 caused ectopic expression of pMADS3 (Shibuya et al 2009).…”
mentioning
confidence: 99%